2016
DOI: 10.1210/jc.2015-3564
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Paralysis as a New Phenotype of Resistance to Thyroid Hormone Syndrome in a Chinese Male Adult

Abstract: This is the first report of periodic paralysis as a new phenotype of RTH syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…HP with hypothyroidism has been reported on 15 occasions previously (16 adults, 2 children). [ 4 5 6 7 8 9 10 11 12 ] Eleven (11/18) patients with HP had hypokalemic periodic paralysis (HPP). One patient had resistance to thyroid hormone and was already on L-thyroxine without improvement in his episodic paralysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HP with hypothyroidism has been reported on 15 occasions previously (16 adults, 2 children). [ 4 5 6 7 8 9 10 11 12 ] Eleven (11/18) patients with HP had hypokalemic periodic paralysis (HPP). One patient had resistance to thyroid hormone and was already on L-thyroxine without improvement in his episodic paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…One patient had resistance to thyroid hormone and was already on L-thyroxine without improvement in his episodic paralysis. [ 9 ] Both our patients came with their first episodes of weakness. Five reports had females with both DRTA and hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…GD is still the most common cause of TPP; however, reported TPP cases were diverse [10] . A recent case report of Chinese patient with resistance to β-subunit of thyroid hormone (RTH) presented with TPP added to the list of cause of TPP and challenged the concept of RTH manifestations [18] . In GD patients with TPP, many reports showed that TPP was a sole initial presentation and other thyrotoxic symptoms and signs could be overlooked [13] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Studistudi elektrofisiologi saat ini menyebutkan bahwa defek yang fundamental pada hipokalemia periodik paralisis melibatkan peningkatan permeabilitas membran natrium otot. 13,14 Tampilan klinis yang paling menonjol dari hipokalemia adalah pada sistem neuromuskular, walaupun sistem lainya seperti kardiovaskular dan gastrointestinal dapat juga terkena. Beberapa pasien mengeluhkan kelemahan otot, terutama pada ekstremitas bawah, dan kelemahan umum otot rangka merupakan keadaan umum pada kekurangan kalium yang berat.…”
Section: Diskusiunclassified
“…Kelemahan biasanya terjadi pada otot kaki dan tangan, tetapi terkadang dapat mengenai otot mata, otot pernafasan, dan otot untuk menelan, yang mana kedua keadaan terakhir ini dapat berakibat fatal. 13,15 Pada saat serangan paralisis dan disertai hipokalemia yang nyata, pemberian suplementasi kalium klorida (KCl) dapat dilakukan untuk mencegah komplikasi berat kardiopulmonal. Suplementasi KCl dapat diberikan melalui jalur intravena, oral, maupun keduanya.…”
Section: Diskusiunclassified